Analisis Tekanan Pori dan Karakteristik Overpressure pada Lapangan “GEO”, Cekungan Sumatra Selatan - Rizky Andra Prasetya; Budhi Setiawan (Journal of Applied Geoscience and Engineering, 2026)
The presence of abnormal pore pressure zones in the South Sumatra Basin represents a significant technical challenge in drilling operations, with the potential to trigger serious incidents such as kicks and blowouts if not accurately predicted in advance. This study aims to estimate pore pressure values, characterize overpressure generation mechanisms, and identify their spatial distribution in the "GEO" Field, South Sumatra Basin. Pore pressure estimation was conducted using the Eaton method based on sonic log data through the construction of a Normal Compaction Trend (NCT) curve across four drilling wells, which was subsequently integrated with Gas While Drilling (GWD) data analysis as an independent validation approach. The results identified two genetically distinct overpressure mechanisms operating at different stratigraphic levels. Loading mechanism overpressure zone, attributed to disequilibrium compaction was consistently identified in association with the Air Benakat Formation and Gumai Formation intervals at depth ranges of 530–1,623 mTVD, with pore pressure values ranging from 797 to 2,811 psi. Unloading mechanism overpressure zone, characterized by distinctive sonic log and resistivity reversal phenomena, was identified within the Talang Akar Formation interval, with pore pressure values ranging from 1,254 to 2,893 psi, consistently higher than those observed in the loading zone. The spatial distribution of both overpressure zones is regional in nature and stratigraphically consistent across all analyzed wells. These findings provide a scientific contribution as the primary basis for optimizing drilling mud weight planning and casing design, thereby effectively mitigating Non-Productive Time (NPT) risks in future drilling operations at the "GEO" Field.